Self-medication with antibiotics: prevalence, practices and related factors among the Pakistani public - Aslam, Adeel; Mohd Zin, Che Suraya; Jamshed, Shazia; Ab Rahman, Norny Syafinaz; Ahmed, Syed Imran; Pallós, Péter; Gajdács, Márió (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Abstract: Self-medication with antibiotics (SMA) has become considerably common in developing countries, which is a critical factor for driving antibiotic resistance. Individuals involved in SMA generally do not have adequate knowledge regarding the appropriate use, indications and dosage of these drugs. The objective of the present study was to investigate population SMA practices, knowledge and sociodemographic factors associated with SMA in Islamabad, Pakistan. The study adopted a cross-sectional methodology and data collection was performed through an anonymous, structured and pilot-tested questionnaire, which was interview-administered. Inferential statistics and multivariate logistic regression were performed. Out of 480 participants, 55.6% (n = 267) were male with a mean age of 37.1 10.1 years; the total prevalence of SMA was 32.5%. Ciprofloxacin (42.9%) was the most commonly used antibiotic to treat coughs or colds, a runny nose, flu or sore throat, diarrhea or fevers, which were relevant reasons for SMA. Findings from multivariate logistic regression showed that predictors of SMA were: male gender (95%CI: 0.383–1.005), age (95%CI: 0.317–0.953) and highest level of education (95%CI: 0.961–0.649). Despite reasonable access to healthcare facilities, people are still obtaining antibiotics without prescription, bypassing diagnostic and consultative healthcare services. Thus, the government must implement strict healthcare policies to restrict the sale of antibiotics without prescriptions, while at the same time, targeted public awareness campaigns about the proper use of antibiotics are also required